Living environments of polish seniors - needs and challenges - Katarzyna Domosławska-Żylińska; Marlena Fronk; Magdalena Krysińska; Hanna Marczak; Olga Partyka; Katarzyna Kwiatkowska; Monika Pajewska; Aleksandra Izabela Czerw (Kazimierz Wielki University, 2018)
Demographic changes in Polish population cause an increase in interest of senior citizens. The environment of living of older people is a particularly important issue. It is important to provide seniors with living space that is a comfortable, safe, adequate to the needs and allows for the longest independent functioning of an elderly person. It is a challenge both for public health and for housing policy.